THE USAGE OF MINING VOID IN LIMESTONE MINING FOR MICRO HIDRO POWER PLAN IN PT. SEMEN BATURAJA (PERSERO) TBK - Ahmad Suryantoko; Restu Juniah; Harminuke Eko Handayani (Research Centre of Inorganic Materials and Complexs, 2018)
Pt. Semen Baturaja TBK Persero is one of the state-owned companies engaged in the cement industry, since 1974 located in West Baturaja, Ogan Komering Ulu, South Sumatra Province. PT Semen Baturaja utilizes limestone as the main raw material in making cement by applying surface mining and blasting methods. every end of the mining activity must implement reclamation. one of the post mining activity plans by PT Semen Baturaja Tbk is to utilize voids as a micro hydro power plant. One of the parameters that must be met is the quality of water. The results of water sample testing indicate that the water content in the limestone mining area has a suspended solid content of 17-22 mg / L, with the metal content contained in the water still below the water quality standard. With a void area of 53.94 Ha, it is capability to storing of water, void in the area of the former limestone mining at PT Semen Baturaja has the potential as a source of water for micro-hydro power plants